Information system for maintaining a database of geobotanical descriptions while studying a landscape; IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Shchukova K. (Control science and system engineering, 2015)
Title screen